EFEKTIVITAS MODEL PEMBELAJARAN MENULIS ARGUMENTASI MELALUI STRATEGI THINK TALK WRITE BERBASIS MEDIA AUDIOVISUAL DI SMA - Suci Rizkiana; Menik Widiyati (p-ISSN 2356-0576, 2018)
Abstract: The aim of this research is to know the effectiveness of the use of learning model towrite argumentation essay trough think talk write strategy based on audio visual media in Senior High Sechool. This research is an experiment research trough static group comparison design. The research subject is debided into three school group category. They are good, medium, and decreaze. Three school decided to be the research subject are SMA N 7 Purworejo, SMA N 5 Purworejo, and SMA N 6 Purworejo. The data analysis is using SPSS 21 program. The data collecting technique are trough observation, interview, questionare and test. Based on the result of independent sample T-test. It is derived sig (0.000) < 0.05, so there is a differences between experiment group and control group. The result of writing argumentation skill, the student used subject of think talk write strategi based on audio visual media is more effective than the achievement of student taughy through conventional learning model. Kata kunci: learning model, think talk write strategi, audio visual media, and SMA.